Pengaruh Beban Pajak, Ukuran Perusahaan, Dan Debt Covenant Terhadap Keputusan Transfer Pricing - Sri Devina; Juitania Juitania (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of tax burden, company size, and debt covenant on transfer pricing in Non-Cyclical Consumer Sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The sampling technique used in this study is purposive sampling, with a quantitative research approach. The data used are secondary data, namely the companies' annual financial statements. The sample in this study consists of 15 Non-Cyclical Consumer Sector companies observed over 5 (five) years, resulting in 75 observation units. Hypothesis testing in this study uses panel data regression analysis with Eviews version 12 software. The results of this study indicate that the variables of tax burden and debt covenant affect transfer pricing, while company size does not affect transfer pricing. Simultaneously, tax burden, company size, and debt covenant affect transfer pricing.